Політичні репресії на Волині (1939–1953 рр.): історіографічний аспект - Довбня, О. А.; Dovbnia, Olha (Східноєвропейський національний університет імені Лесі Українки, 2017)
Висвітлено сучасний стан дослідження українськими істориками проблеми політичних репресій щодо населення Волині в 1939-1953 рр. У результаті виокремлено п’ять історіографічних груп. У межах кожної із них проаналізовано здобутки та окреслено перспективи подальших науково-історичних досліджень проблеми.It is described the current state of study by Ukrainian historians of the problem of political repression against the population of Volyn region in the years 1939-1953. The main aim of the article is to analyze the main historiographical approaches to the studying of a given problem, the degree of its scientific development, as well as the prospects for further investigation of the forms, methods and consequences of implementing the repressive policy of the Soviet state against the population of Volyn region in the years 1939-1953.
Repressions in the Volyn Region (1939-1953 years): Historiographical Aspect
Keywords: історіографічний аналіз; тоталітарний режим; радянізація; репресивна система; репресії; депортації; historiographical analysis; totalitarian regime; sovietization; a repressive system; repression; deportation